Gen-miR-5 derived from Gentianella acuta inhibits PFKP to prevent fibroblast activation and alleviate myocardial fibrosis - Hongyao Ge; Zhenyu Du; Weizhe Liu; Weizhe Liu; Weizhe Liu; Letian Wang; Junyang Li; Gaoshan Yang; Gaoshan Yang; Gaoshan Yang; Aiying Li; Aiying Li; et al. (Frontiers in Pharmacology)
IntroductionMyocardial fibrosis (MF) is a key pathological change in heart failure, and lactate a product of glycolysis, is an important component affecting the process of MF. miRNAs derived from Gentianella acuta (G. acuta) have been shown to effectively treat cardiac remodeling. However, whether G. acuta-derived Gen-miR-5 can effectively improve MF remains to be elucidated. This study seeks to explore the pharmacological effects and underlying molecular mechanisms of Gen-miR-5 in the context of Angiotensin II (Ang II) -induced MF.MethodsA mouse model of MF was established by subcutaneous infusion of Ang II using osmotic pumps, and then administration of Gen-miR-5 by injection. The effects of Gen-miR-5 in reducing MF and exerting cardioprotective actions were evaluated through pathological morphological analysis and echocardiography. The targeting effect of Gen-miR-5 on PFKP was assessed through dual-luciferase reporter gene assays. Cardiac fibroblasts (CFs) migration abilities were evaluated through wound healing assay and transwell assays. Additionally, the role of Gen-miR-5 in fibroblast activation was investigated using gain- and loss-of-function experiments, and immunofluorescence.ResultsThis study identified six novel specific miRNAs in G. acuta, among which Gen-miR-5 can be absorbed by mice, stably exists in cardiac tissue, and targets the PFKP 3’ UTR to exert cross-kingdom regulatory effects. PFKP, as a key rate-limiting enzyme in the glycolytic pathway, increases lactate accumulation and promotes the proliferation and migration of CFs, thereby facilitating the development of MF. In contrast, Gen-miR-5 alleviates MF by inhibiting this process.DiscussionIn conclusion, we have elucidated for the first time the pharmacological effects of Gen-miR-5, derived from G. acuta, in inhibiting MF. Gen-miR-5 exerts its cardioprotective effects by targeting and inhibiting the expression of the key glycolytic enzyme PFKP, induced by Ang II, regulating lactate metabolism in fibroblast, and preventing the transformation of fibroblasts into myofibroblasts, ultimately alleviating MF. This study demonstrates that Gen-miR-5 is a potential therapeutic agent for improving cardiac remodeling.